Elucidating cell-penetrating peptide mechanisms of action for membrane interaction, cellular uptake, and translocation utilizing the hydrophobic counter-anion pyrenebutyrate. - Guterstam, P; Madani, F; Hirose, H; Takeuchi, T; Futaki, S; Andaloussi, S; Gräslund, A; Langel, U (2009)
Cell-penetrating peptides (CPPs) are membrane permeable vectors recognized for their intrinsic ability to gain access to the cell interior. The hydrophobic counter-anion, pyrenebutyrate, enhances cellular uptake of oligoarginine CPPs. To elucidate CPP uptake mechanisms, the effect of pyrenebutyrate on well-recognized CPPs with varying hydrophobicity and arginine content is investigated. The cellular CPP uptake and CPP-mediated oligonucleotide delivery is analyzed by fluorescence activated cell sorting, confocal microscopy, and a cell-based splice-switching assay. The splice-switching oligonucleotide is a mixmer of 2'-O-methyl RNA and locked nucleic acids delivered as a non-covalent complex with 10-fold molar CPP excess. CPP-induced membrane perturbation on large unilamellar vesicles is investigated in calcein release experiments. We observed that pyrenebutyrate facilitates cellular uptake and translocation of oligonucleotide mediated by oligoarginine nonamer while limited effect of pyrenebutyrate on more hydrophobic CPPs was observed. By combining the different experimental results we conclude that the pathway for cellular uptake of oligoarginine is dominated by direct membrane translocation, whereas the pathway for oligoarginine-mediated oligonucleotide translocation is dominated by endocytosis. Both mechanisms are promoted by pyrenebutyrate and we suggest that pyrenebutyrate has different sites of action for the two uptake and translocation mechanisms.